2017
DOI: 10.5114/aoms.2017.65229
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and metabolic disorders – where are we heading?

Abstract: MicroRNAs (miRNAs, miRs) are short, non-coding molecules engaged in normal functioning of eukaryotic cells, as negative regulators of gene expression. Since the first discovery of miRNA in the early 1990s, hundreds of different miRNAs and their targets have been identified. A growing number of studies have aimed to search for microRNAs which have a key role in the regulation of insulin signaling and metabolic homeostasis. Recent evidence indicates that dysregulation of miRNA expression is involved in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 79 publications
0
35
0
Order By: Relevance
“…MiRNAs are master regulators that control many biological processes including cell proliferation, differentiation, apoptosis, and development [ 127 ]. Moreover, they regulate genes involved in metabolic processes such as glucose homeostasis, insulin signaling, pancreatic beta-cell function, lipid metabolism, and inflammation [ 128 ]. Their dysregulation was reported during many metabolic conditions, including obesity, T2D, and cardiovascular disease [ 129 , 130 , 131 ].…”
Section: Micrornasmentioning
confidence: 99%
“…MiRNAs are master regulators that control many biological processes including cell proliferation, differentiation, apoptosis, and development [ 127 ]. Moreover, they regulate genes involved in metabolic processes such as glucose homeostasis, insulin signaling, pancreatic beta-cell function, lipid metabolism, and inflammation [ 128 ]. Their dysregulation was reported during many metabolic conditions, including obesity, T2D, and cardiovascular disease [ 129 , 130 , 131 ].…”
Section: Micrornasmentioning
confidence: 99%
“…There are different theories about obesity's mechanisms, such as inflammation, inflammasome activation, insulin resistance, 2 Arch Med Sci adipokine balance, and abnormalities in lipid metabolism and endothelial function [4]. Some of the newest data have shown that obesity is characterized by low-grade chronic inflammation caused by increased secretion of pro-inflammatory cytokines and adipokines by the macrophages and adipocytes present in adipose tissue [5]. Almost all obese patients should have additional behavioural treatment.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are a class of small non-coding RNAs, which have been found to have various functions and complicated regulatory mechanisms, and they take part in almost all physiological or pathological cytobiological characteristics, includ ing apoptosis, cell proliferation, and chemotherapy resistance [5][6][7][8]. Some studies have reported that MiRNA-610 was low-expressed in various malignant tumours, including HCC, colorectal cancer, and gastric cancer [9][10][11].…”
Section: Introductionmentioning
confidence: 99%